2008
DOI: 10.1002/jhet.5570450401
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the chemistry of 4‐ thiazolidinones

Abstract: This review article includes a recent development in the chemistry of 4-thiazolidinones. Structure, basicity, synthetic aspects, reactions, and applications were also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 104 publications
0
24
0
Order By: Relevance
“…1,3-thiazolidin-4-ones, also known as thiazolidin-4-ones, are known to have a very wide range of biological activity (Tripathi et al, 2014;Jain, Vaidya, Ravichandran, Kashaw, & Agrawal, 2012;Abhinit, Ghodke & Pratima, 2009;Hamama, Ismail, Shaaban & Zoorob, 2008;Singh, Parmar, Raman, Virgil & Stenberg, 1981;Brown, 1961), so much that some have referred to it as a "magic moiety" or "wonder nucleus" (Jain et al, 2012). The S-oxides may show enhanced activity; for example, Miller and coworkers converted one 4-thiazolidinone to its sulfoxide and sulfone and reported that the oxides showed greater activity against some cancer cell lines than the sulfide (Gududuru, Hurh, Dalton & Miller, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…1,3-thiazolidin-4-ones, also known as thiazolidin-4-ones, are known to have a very wide range of biological activity (Tripathi et al, 2014;Jain, Vaidya, Ravichandran, Kashaw, & Agrawal, 2012;Abhinit, Ghodke & Pratima, 2009;Hamama, Ismail, Shaaban & Zoorob, 2008;Singh, Parmar, Raman, Virgil & Stenberg, 1981;Brown, 1961), so much that some have referred to it as a "magic moiety" or "wonder nucleus" (Jain et al, 2012). The S-oxides may show enhanced activity; for example, Miller and coworkers converted one 4-thiazolidinone to its sulfoxide and sulfone and reported that the oxides showed greater activity against some cancer cell lines than the sulfide (Gududuru, Hurh, Dalton & Miller, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…IR (KBr) spectra were recorded on a Perkin Elmer SP-880 spectrometer and from samples of sufficient solubility. 1 H-NMR spectra were measured on a Varian 270 MHz spectrometer on DMSO-d 6 as solvent and TMS as an internal standard. Chemical shifts are reported in δ units (ppm).…”
Section: Methodsmentioning
confidence: 99%
“…Diverse pharmacological properties have been associated with thiazole derivatives [1][2][3]. These pharmacological activities have been attracted special attention to prepare a new class of thiazole derivatives carrying antipyrinyl moiety because of their applications in the field of pharmaceuticals [4][5][6] and antibacterials [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The five-membered 1,3-thiazolidin-4-ones are known to have a broad array of biological activity (Jain, Vaidya, Ravichandran, Kashaw & Agrawal, 2012, Abhinit, Ghodke & Pratima, 2009, Hamama, Ismail, Shaaban & Zoorob, 2008, Singh, Parmar, Raman & Stenberg, 1981, Brown, 1961, Tripathi et al, 2014, Prabhakar, Solomon, Gupta & Katti, 2006. Compounds in this family include active pharmaceuticals thiazolidomycin (anti-streptomyces species), pioglitazone (hypoglycemic for treatment of diabetes), etoziline (anti-hypertensive), and ralitoline (anti-convulsant) (Brown, 1961, Tripathi et al, 2014.…”
Section: Introductionmentioning
confidence: 99%